Hypertensive disorders in pregnancy and the general practitioner: A vignette and lessons to learn - J. Moodley (South African Family Practice)
In South Africa, the general practitioner is often the first health professional to provide care and health advice to pregnant women. Estimation of blood pressure levels is an essential basic step, particularly in pregnant women. Hypertensive disorders occur frequently in pregnancy and are significant causes of maternal morbidity and mortality. General practitioners should be aware of the complications associated with hypertension and recognise that severe hypertension requires prompt, gradual and sustained lowering of blood pressure, intensive counselling and early referral to an appropriate hospital.